Prognostic Value of Aspartate Transaminase/Alanine Transaminase Ratio in Patients With Hepatitis B Virus-Related Hepatocellular Carcinoma Undergoing Hepatectomy - Mo, Qiuyan; Liu, Yingchun; Zhou, Zihan; Li, Runwei; Gong, Wenfeng; Xiang, Bangde; Tang, Weizhong; Yu, Hongping (Frontiers in Oncology, 2022)
Background: Aspartate transaminase/alanine transaminase (De Ritis) ratio is a good predictor of liver function damage, but its prognostic value in patients with hepatocellular carcinoma (HCC) undergoing hepatectomy remains unclear. This study aimed to assess the association of the De Ritis ratio with overall survival (OS) among hepatitis B virus (HBV)-related HCC patients undergoing hepatectomy. Methods: A total of 1,147 HCC patients were recruited. Cox regression analysis was used to identify the independent risk factors. Restricted cubic spline (RCS) was used to evaluate the association between De Ritis ratio and mortality risk. Nomogram was constructed to determine the predictive power of the De Ritis ratio. Results: Multivariate Cox regression analysis revealed that the tertile of De Ritis ratio was an independent risk factor for mortality. After adjustment for confounding factors, the adjusted hazard ratios (HRs) with corresponding 95% confidence intervals (CIs) of mortality for the 2 st tertile and 3 st tertile were 1.175 (0.889 - 1.554) and 1.567 (1.199 - 2.046), respectively. RCS confirmed a non-linear association between the natural logarithm of De Ritis ratio and the risk of mortality (P for nonlinearity = 0.0375). The nomogram showed that the natural logarithm of De Ritis ratio contributed the most to the prediction of prognosis in HBV-related HCC patients, and Harrell’s C-index was 0.680 with a 95% CI of 0.645 - 0.715. Conclusion: De Ritis ratio is an independent predictor for OS in HBV-related HCC patients undergoing hepatectomy, which allows for prognostic stratification of patients, hence, individualized treatment and follow-up.